Advancements in lamb wave high-frequency devices using diamond-like carbon (DLC) coatings - Jatinder Pal Singh; Ajay Kumar Sao; Babita Sharma; Satyam Garg; Anjali Sharma; Reema Gupta; Lokesh Rana; Mallika Verma; Akhilesh Pandey; Archibald Theodore Nimal; Upendra Mittal; Amit Kumar Vishwakarma; et al. (Chemical Physics Impact)
Diamond-like carbon (DLC) stands as a material of profound scientific and technological importance, owing to its exceptional blend of mechanical, tribological, and chemical properties. Lamb wave devices, vital in sensing, communication, and structural health monitoring, require efficient surface acoustic wave (SAW) propagation for their diverse applications. Theoretical studies suggest that DLC coatings can accelerate SAWs due to their high elastic constant and low mass density, making them highly desirable for enhancing SAW device performance. In the present work, a process for reliable deposition of DLC films on the SiO2/Si membrane has been investigated, aiming to optimize their functionality. MEMS (micro-electromechanical system) technology was adopted for the development of SiO2/Si membrane-based Lamb wave devices utilising piezoelectric ZnO thin film and high-velocity DLC coating. The DLC films were coated on the SiO2/Si membrane using the Hot Filament Chemical Vapor Deposition (HFCVD) method followed by deposition of a piezoelectric layer of ZnO film through RF magnetron sputtering. The patterning of aluminium electrodes for the fabrication of Lamb wave devices was carried out using lithography. The frequency response of the Lamb wave devices prepared without and with DLC coatings was studied and it was found that the Lamb wave devices without DLC coatings showed a return loss of -27.97 dB at a frequency of 286 MHz. However, with the incorporation of DLC coating, the frequency increased to 345 MHz with a lower return loss of -19.46 dB. The outcomes of this research underscore the potential of DLC coatings to optimize the Lamb wave device functionalities, promising enhanced performance and broader applications. Continued exploration and refinement in this field hold promise for further enhancing DLC coatings and broadening the scope of Lamb wave device applications.